Pedobarographic Analysis Following Pemberton's Pericapsular Osteotomy for Unilateral Developmental Dysplasia of the Hip. Issue 23 (June 2015) - Xu, Chao; Yan, Ya-Bo; Zhao, Xiong; Wen, Xin-Xin; Shang, Lei; Huang, Lu-Yu; Lei, Wei; Polisner., Stuart Barry
<x xml:space="preserve">Abstract</x> Abstract Successful clinical and radiographic outcomes have been reported in patients with unilateral developmental dysplasia of the hip (DDH) following Pemberton pericapsular osteotomy (PPO). However, residual gait deviations are seen in both the affected and unaffected limbs. To date it is not known whether these deviations result in abnormal plantar pressure in such patients. This study investigated this possibility by performing pedobarographic, clinical, and radiographic examinations after PPO in 20 patients (age: 102.5 ± 19.0 months) with unilateral DDH who underwent PPO at 34.2 ± 9.8 months of age. Plantar pressure was evaluated using the Footscan pressure plate (RsScan International, Olen, Belgium). Each foot was subdivided into 10 zones and peak pressure, force–time integral as a percentage of total FTI, and contact time as a percentage of total stance time was estimated. The minimum duration of follow-up was 24 months (mean: 68.3 ± 20.3 months). The data were compared with 20 age- and weight-matched healthy controls. Despite clinical and radiographic examinations showing satisfactory results according to modified McKay and Severin criteria, significant differences in plantar pressure parameters were identified between the affected limbs, the unaffected limbs, and normal controls. No significant differences were found between patients classified as "excellent or good" and those rated as "fair" according to the modified Severin criteria. Pedobarographic results showed the existence of the residual plantar pressure deviations during walking in patients treated with PPO for unilateral DDH. Longer follow-up will be needed to more fully evaluate the effect of these deviations on gait.